2021
DOI: 10.1128/aac.00330-21
|View full text |Cite
|
Sign up to set email alerts
|

MAB_2355c Confers Macrolide Resistance in Mycobacterium abscessus by Ribosome Protection

Abstract: Macrolide resistance is always a concern when treating Mycobacterium abscessus infections. MAB_2355c was identified previously as a possible new factor that confers the intrinsic resistance of 194 clinical M. abscessus isolates to clarithromycin. Herein, the potential mechanism by which MAB_2355c exerts macrolide resistance was explored by bioinformatics analysis, MAB_2355 cloning and protein purification, ATP hydrolysis assay, gene knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Among the genes regulated by Lsr2 in both Mabs-S and Mabs-R, we have identified four genes ( eis2, MAB_1409c, MAB_2355 c, and erm41 ) encoding proteins modifying the activity of aminoglycoside and macrolide antibiotic families, both widely used in the clinical treatment of M. abscessus ( 9 , 48 53 ). Our RNA-seq data show that Lsr2 activates these antimicrobial resistance genes, exhibiting higher expression in wild-type strains ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the genes regulated by Lsr2 in both Mabs-S and Mabs-R, we have identified four genes ( eis2, MAB_1409c, MAB_2355 c, and erm41 ) encoding proteins modifying the activity of aminoglycoside and macrolide antibiotic families, both widely used in the clinical treatment of M. abscessus ( 9 , 48 53 ). Our RNA-seq data show that Lsr2 activates these antimicrobial resistance genes, exhibiting higher expression in wild-type strains ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the genes regulated by Lsr2 in both Mabs-S and Mabs-R, we have identified four genes ( eis2, MAB_1409c, MAB_2355c and erm41 ) encoding proteins modifying the activity of aminoglycosides and macrolides antibiotics families, both widely used in the clinical treatment of M. abscessus (9, 4853). Our RNA-seq data shows that Lsr2 activates these antimicrobial resistance genes, exhibiting higher expression in wild-type strains ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Their mode of action involves binding to the 50S ribosomal subunit in bacteria, which results in the inhibition of protein synthesis ( Dinos, 2017 ). Macrolides remain the core drugs for treating Mab infections ( Guo et al, 2021 ). In certain NTMs, exposure to macrolides triggers the production of specific enzymes that modify the drug’s target binding site.…”
Section: Mechanisms Of Mab Resistance To Current A...mentioning
confidence: 99%
“…More recently, Guo et al identified another macrolide-resistant gene in Mab . The gene MAB_2355c exhibits ATP hydrolysis activity and contributes to macrolide resistance by protecting ribosomes ( Guo et al, 2021 ). Expression of MAB_2355c mRNA is significantly upregulated after exposure to macrolides compared to other ribosome-targeting antibiotics.…”
Section: Mechanisms Of Mab Resistance To Current A...mentioning
confidence: 99%